Detection of multimycotoxins in camel feed and milk samples and their comparison with the levels in cow milk - Randa Zeidan (14778388) (2023)
Camel milk has been considered as an important source of nutrients and is commercialized in many countries of the world including the Middle East. This study aimed to investigate the presence of mycotoxins in camel feed and milk samples in comparison with the cow milk. Fumonisins (FUM), ochratoxin A (OTA), and zearalenone (ZEN) were detected in 14%, 39%, and 39% of the tested camel feed samples, respectively. Among the tested camel feed samples, 8.3% and 5.6% were co-contaminated with OTA+FUM and FUM+ZEN, respectively. In the case of milk samples, 46.15% of camel and 63.63% of cow were found contaminated with aflatoxin M1 (AFM1). In total, 16.2% and 8.1% of the milk samples were simultaneously contaminated with two and three mycotoxins, respectively. Although the levels of individual mycotoxins in the camel feed and milk samples were within the European Union (EU) permissible limits, their co-occurrence may pose severe risk to human and animal health due to possible additive and/or synergistic toxicities. Other Information Published in: Food Science & Nutrition License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/fsn3.2677